Resepsi Konsumen terhadap Brand Image Produk Fashion Sophie Martin Paris - Lailatul Munawaroh; Ainur Rochmaniah (Kanal: Jurnal Ilmu Komunikasi, 2017)
The purpose of this study described consumer receptions of the fashion product brand image Sophie Martin Paris. This qualitative research used interview data collection techniques to fashion product consumer Sophie Martin Paris. Location in this study at Business Center (BC) Khusnul Khotimah Ngoro Mojokerto Sub-district. The results of this study indicated that consumer reception of fashion products Sophie Martin Paris showed a positive thing. Consumers provided a brand image or a good brand image of the products were distributed by Sophie Martin Paris company. That way audiences would trust and interested in buying and delivering positive assumptions about a product already distributed.